Magnitude and direction of interlimb asymmetry and the association of interlimb asymmetry with physical performance in judo athletes with visual impairment - Carvalho, M.; Athayde, M. S. da S.; Vieira, A.; Detanico, D.; Kons, R. L. (Perceptual and Motor Skills, 2024)
For judo athletes with visual impairments and their coaches, understanding possible muscle adaptations can be challenging. As it is commonplace for these adaptations to include interlimb asymmetry, we analyzed the magnitude and direction of interlimb asymmetry in judo athletes with visual impairments and verified the association of this asymmetry with their unilateral physical performances. Participants were 18 elite judo athletes (10 male, 8 female) with visual impairments. These athletes performed three physical tests: countermovement jump (CMJ), medicine ball throw (MBT), and handgrip strength (HGS), while we conducted unilateral right and left side assessments using the interlimb asymmetry equation for each physical test. Our main results showed that the CMJ and MBT tests presented asymmetry values above 10%; with CMJ significantly higher than HGS (p = 0.050), and with inconsistencies across the three tests in the direction of interlimb asymmetry (k = -0.22-0.26). Unilateral CMJ (left limb) was negatively correlated with asymmetry (r = -0.51; p = 0.031), and unilateral MBT (right limb) was positively correlated with asymmetry (r = 0.52; p = 0.024). Based on these results, coaches should prioritize regular assessments of interlimb asymmetry using these specific tests. This data can guide the construction of training programs aimed at minimizing asymmetry and enhancing overall physical performance. Continuous monitoring and adjustment of training strategies based on asymmetry findings are crucial for optimizing muscle balance in judo athletes with visual impairments.